012: COMMUNITY-BASED ECOMPLIANCE; CURBING AND PREVENTING DRUG RESISTANT TUBERCULOSIS. (24th August 2015) - Batra, Shelly; Ahuja, Sandeep; Harshe, Navika; Sinha, Abhishek
Abstract : Background: OpASHA, in partnership with Microsoft Research, developed and deployed eCompliance—a biometric attendance system to accurately track the doses of all patients. eCompliance exists to solve the problem of inadequate, inconsistent, often nonexistent quality treatment for TB patients in hard to reach places. Objectives: eCompliance is a biometric based system to improve adherence and accountability in the area of healthcare delivery to the disadvantaged. eCompliance seeks to increase successful completion in the full treatment regimen, thereby decreasing the default rate and incidence of drug resistant Tuberculosis. Methods: eCompliance uses fingerprint verification and mobile SMS messaging to ensure thatpatients are adhering to their treatment regimens. During each patient visit, the patient and healthcare worker simultaneously scan their fingerprint in the system, the medication is dispensed, and the treatment is recorded in the system's database. If a patient misses a dose, an SMS message alert is sent to the patient, healthcare worker and supervisor. The healthcare worker is then responsible to meet the patient within 24–48 hours to administer and record the treatment. Result: Reduction of the number of missed doses: reduced OpASHA's default rate to less than 3.2% compared to default rates of 11.8% at other South Delhi TB treatment centers.Program managers are able to offer targeted counseling and supervision.Prevents the manipulation of handwritten patient cards and other manual records: Reduces absenteeism and unnecessary waste of time by health workers by verifying employee presence. Digitized attendance records: eCompliance automates the generation of all reports, which can be simultaneously viewed by all operational management staff. Columbia University replicated OpASHA's care model in Uganda using eCompliance and achieved 100% patient adherence to TB treatment. Conclusion: Ensuring that patients are adhering to their medication regimens can dramatically reduce the risk of developing drug resistant diseases and therefore significantly reduce treatment costs.eCompliance, coupled with OpASHA's community model, has the proven ability to both curb and prevent drug resistant TB. eCompliance can be applied to any health issue that requires long term care, physical presence of the patient/beneficiary, accurate data, transparency and high productivity.